Coverage polio vaccine in Brazilian states and regions (2019-2022) (Research, Society and Development, 2023)
Introduction: Poliomyelitis was eliminated in Brazil in the 1990s due to the success of vaccination campaigns. However, the Covid-19 pandemic period and the antivaccine movements stand out as warning factors to the possible return of the circulation of the virus that causes this disease, requiring continuous monitoring in the territory. This study aimed to present the polio vaccine coverage in the states and regions of Brazil in the period 2019 to 2022, relating it to socioeconomic variables, pandemic by Covid-19 and antivaccine movements. Methodology: Descriptive observational study, whose data were obtained from the National Immunization Program Information System made available by the DATASUS system. Results: In the period studied, no state reached the goal proposed by the Ministry of Health, one of the reasons being not only the pandemic, but also the spread of false news and socioeconomic factors, such as education and income. Conclusion: There are important differences in the coverage of the booster dose of the vaccine in the years 2019-2022, and the low percentage presented is worrisome, since the administration of the vaccine is what ensures the child's long-term immunity.